1996
DOI: 10.1007/bf01412310
|View full text |Cite
|
Sign up to set email alerts
|

A new, more dependable methodology for the use of transcranial Doppler ultrasonography in the management of subarachnoid haemorrhage

Abstract: The role of transcranial Doppler ultrasound (TCD) in clinical decision making about vasospasm due to subarachnoid haemorrhage (SAH), shows a great variation according to neurosurgical clinics. In this prospective study, a total of 143 patients, admitted to Marmara University Department of Neurosurgery between January 1991 to March 1995 and treated surgically with the diagnosis of aneurysmal SAH, were examined by TCD. Eighty of these patients fulfilled the requirements for inclusion. In order to increase clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We found that the detection of HDI was clearly associated with the development of delayed cerebral ischemia after SAH, but no ischemic complications followed the registration of vasospasm without HDI. Although a positive correlation between arterial vasospasm and the development of delayed ischemia has been confirmed in a number of studies, 12,15,16,18,24,38 several authors have reported on patients who tolerated severe angiographically confirmed vasospasm, 12 as well as extreme increases in BFV values, 5,6,29 with no neurological deterioration. At the same time, a number of injurious complications besides vasospasm have been associated with DCI and poor clinical outcome after SAH.…”
Section: Relationship Between Hdi and Delayed Cerebral Ischemiamentioning
confidence: 94%
“…We found that the detection of HDI was clearly associated with the development of delayed cerebral ischemia after SAH, but no ischemic complications followed the registration of vasospasm without HDI. Although a positive correlation between arterial vasospasm and the development of delayed ischemia has been confirmed in a number of studies, 12,15,16,18,24,38 several authors have reported on patients who tolerated severe angiographically confirmed vasospasm, 12 as well as extreme increases in BFV values, 5,6,29 with no neurological deterioration. At the same time, a number of injurious complications besides vasospasm have been associated with DCI and poor clinical outcome after SAH.…”
Section: Relationship Between Hdi and Delayed Cerebral Ischemiamentioning
confidence: 94%
“…Surgical manipulation, which was postulated to be the cause of the reversible increase in V m due to increased vasospasm in the TCD follow-up study of aneurysmal subarachnoid hemorrhage, might explain the delay in normalization of V m . 24 PI, which is a mathematical ratio, seems to be less affected by immediate postoperative reversible vasospasm. Therefore, one can conclude that PI is a more dependable parameter to evaluate the physiological success of the operation in early postoperative days.…”
Section: Tcd Sonography In Hemodynamicmentioning
confidence: 94%
“…The pulsatility index (PI) was obtained for each intracranial artery as (Peak systolic velocity-end diastolic velocity)/mean flow velocity. [ 4 , 5 , 10 , 11 ] A value of 0.6–1.1 represented the normal range for the PI in the intracranial arteries. [ 4 , 5 , 10 , 11 , 12 ]…”
Section: Methodsmentioning
confidence: 99%